Spoligotyping of Mycobacterium tuberculosis – Comparing in vitro and in silico approaches - Bakuła, Zofia; Dziurzyński, Mikołaj; Decewicz, Przemysław; Bakonytė, Daiva; Vasiliauskaitė, Laima; Nakčerienė, Birutė; Krenke, Rafał; Stakėnas, Petras; Jagielski, Tomasz (Infection, genetics and evolution, 2023)
Spoligotyping is one of the molecular typing methods widely used for exploring the genetic variety of Mycobacterium tuberculosis. The aim of this study was to compare the spoligoprofiles of M. tuberculosis clinical isolates, obtained using in vitro and in silico approaches. The study included 230 M. tuberculosis isolates, recovered from Poland and Lithuania between 2018 and 2021. Spoligotyping in vitro was performed with a commercially available kit. Whole genome sequencing (WGS) was done with Illumina NovaSeq 6000 sequencer. Spoligotype International Types (SITs) were assigned according to the SITVIT2 database or using three different in silico tools, and based on WGS data, namely SpoTyping, SpolPred, and lorikeet. Upon in vitro spoligotyping, the isolates produced 65 different spoligotypes. Spoligotypes inferred from the WGS data were congruent with in vitro generated patterns in 81.7% (188/230) for lorikeet and 81.3% (187/230) for SpolPred and SpoTyping. Spacers 18 and 31 produced the highest ratio of discrepant results between in vitro and in silico approaches, with their signals discordantly assigned for 15 (6.5%) and 9 (3.9%) isolates, respectively. All three in silico approaches used were similarly efficient for M. tuberculosis spoligotype prediction. However, only SpoTyping could predict spoligotypes without a need for manual curation. Thus, we consider it as the most accurate tool. Its use is further advocated by the shortest time of analysis. A relatively high (ca. 20%) discordance between in vitro and in silico spoligotyping results was observed. While we discourage comparing conventional spoligotyping with in silico equivalents, we advise the use of the latter, as it improves the accuracy of spoligopatterns, and thus depicts the relatedness between the isolates more reliably. •Spoligoprofiles of 230 M. tuberculosis clinical isolates, obtained using in vitro and in silico approaches were compared.•Since SpoTyping was the most time efficient tool and did not require manual curation, we advise to use it for in silico prediction of spoligotypes.•A relatively high (ca. 20%) discordance between in vitro and in silico spoligotyping results was observed.•We advise the use of the in silico spoligotyping, as it improves the accuracy of spoligopatterns, and thus depicts the relatedness between the isolates more reliably.